POTENTIAL AND TRENDS OF PULSES PRODUCTION IN FAISALABAD - Ramsha Rashid; Rabia; Iqra Zafar Khan; Muhammad Waqas Khan; Durshana Khan; Sohaib Shaukat (International Journal of Contemporary Issues in Social Sciences, 2024)
Major source of vegetable protein are pulses. Demand of pulses is increasing day by day due to increase in population. Year 2016 was declared as the “Year of Pulses” by the United Nations to increase the awareness about the importance of pulses. Consumption of pulses have been increased steadily and import of pulses have been increased in recent years. As compared to other crops prices of pulses are very high. Although, pulses are in demand and currently Pakistan importing pulses to fulfill the demand. Specific end goal is to find out the reasons, why farmers are not considering the importance of pulses cultivation. Study was conducted in tehsil Faisalabad (Sadar). From Faisalabad (Sadar) 4 villages were selected conveniently by keeping in view time and resources. In selected villages there were 712 farmers. Sample size had been calculated by using online website (www.surveysystem.com) keeping confidence level 95% and confidence interval 8 which is 124. Proportionate random sampling was used for the selection of respondents. Sample was drawn by using www.randomizer.org. The data were collected through interview schedule. Statistical Package for Social Sciences (SPSS) was used for data analysis. Farmers said pulses are beneficial crop with mean value 2.24. According to respondents’ pulses are beneficial for soil its mean value was 3.85. Respondents have good knowledge about post-harvest handling of pulses crops with mean value 2.87. At mean value 4.03 respondents get information from fellow farmers. Many respondents get agricultural information from pesticide agents their mean value was 3.80. Middleman monopoly is a hindering factor in pulses cultivation its mean value was 4.32. Due to less agricultural land holding respondents do not grow pulses they just grow major crops such as wheat, rice, maize and vegetables to earn more profit. Findings of the study suggested more extension education campaigns should be launched, provision of machinery on subsidy, availability of inputs at subsidized rates on equality basis, provision of certified seed on equality basis from agriculture department, extension staff should be trained in latest production technology of pulses. Respondents pointed out a desire for the government to set adequate pulses prices so that they may grow pulses.